Qualitative and Quantitative Study on Students’ Critical Thinking of Conceptual E-Scaffolding in Blended Learning Context - Mardikaningsih Agusti; Kurniasari Praharisti; Pradipta Anangga (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
Critical thinking skills are one of the rational thinking skills that students really need in solving problems or conveying ideas. In fact, students' critical thinking abilities are still relatively low. A feasible alternative for developing students' critical thinking skills is by implementing electronic-based scaffolding. This research uses mixed methods with an explanatory research design. The experimental group received conceptual treatment of e-scaffolding blended learning with the Problem-Based Learning model and the control group received no additional treatment. experimental group and control group, the research subjects were first semester students of IKIP Budi Utomo Malang. Because there were two research groups, 46 students were included in the control group. The instruments used in this research were pre-test and post-test. The pre-test consists of 18 multiple choice items with a reliability coefficient of 0.735 and the critical thinking post-test consists of 14 essay questions with a reliability coefficient of 0.762. In addition, semi-structured and think aloud interview guidelines were also used. Quantitative data was obtained from the distribution of pre-test and post-test questions. Meanwhile, qualitative data was obtained from semi-structured interviews and think aloud. Quantitative data was then analyzed using parametric ANACOVA analysis while qualitative data was analyzed using a path analysis model. The results of the research show 1) the critical thinking abilities of students who learn with conceptual e-scaffolding in blended learning in Problem-Based Learning are higher than students who learn with conventional methods, 2) the application of conceptual e-scaffolding in Problem-Based Learning. The link map form in the Problem Based Learning model has a positive effect on students' critical thinking abilities. This is reflected in the behavior and way of thinking of experimental group students which shows the development of critical thinking skills during the learning process. Apart from that, conceptual e-scaffolding in the form of a link map helps students obtain information easily and use it in understanding concepts in geometric optics material